2020
DOI: 10.1016/j.ahj.2020.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on patients with ST-segment elevation myocardial infarction: Insights from a British cardiac center

Abstract: The current study aimed to examine the impact of COVID-19 pandemic on patient-related delay with ST-segment elevation myocardial infarction (STEMI) at a tertiary center in the United Kingdom. The study demonstrated a significant delay in symptom-to-first medical contact and a higher cardiac troponin-I level on admission in patients with STEMI during the COVID-19 pandemic versus the pre-COVID era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 13 publications
6
71
0
3
Order By: Relevance
“…(b) Older patients with an ACS (mainly UA) presented less frequently to the hospitals during the COVID‐19 period; older patients were considered from the start of the outbreak as one of the population groups at highest risk from COVID‐19 and were urged early by mass media and government authorities to avoid social contact and be self‐confined. (c) During the COVID‐19 outbreak, ACS patients presented more frequently with LV systolic impairment, which may serve as a surrogate marker for delayed MI presentation, and is supported by longer times from symptom onset to first medical contact observed for MI patients in other countries 9‐11 …”
Section: Discussionmentioning
confidence: 95%
“…(b) Older patients with an ACS (mainly UA) presented less frequently to the hospitals during the COVID‐19 period; older patients were considered from the start of the outbreak as one of the population groups at highest risk from COVID‐19 and were urged early by mass media and government authorities to avoid social contact and be self‐confined. (c) During the COVID‐19 outbreak, ACS patients presented more frequently with LV systolic impairment, which may serve as a surrogate marker for delayed MI presentation, and is supported by longer times from symptom onset to first medical contact observed for MI patients in other countries 9‐11 …”
Section: Discussionmentioning
confidence: 95%
“…3 ). Several studies have evaluated the delay in first medical contact or door-to-balloon time; (6, 10, 16-18, 21) however, only 1 study, which included 9 patients during the pandemic, assessed all of the stages from symptom-onset to balloon dilatation ( 17 ). Our study provides detailed information about delays at each step in a large nationwide population.…”
Section: Discussionmentioning
confidence: 99%
“…
Figure 4 Summary of reports in literature demonstrating the drop in STEMI volume and relative prevalence of COVID-19. 1 , 2 , 6 , 7 , 11 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 . For each country, the total number of COVID-19 cases, the cases per million, the drop in STEMI volume by percentages and the size of the study are shown.
…”
Section: Discussionmentioning
confidence: 99%